2020
DOI: 10.1080/02626667.2020.1762888
|View full text |Cite
|
Sign up to set email alerts
|

Comparative hydrogeology – reference analysis of groundwater dynamics from neighbouring observation wells

Abstract: Groundwater level fluctuations are caused by spatial and temporal superposition of processes within and outside the aquifer system. Most of the subsurface processes are usually observed on a small scale. Upscaling to the regional scale, as required for future climate change scenarios, is difficult due to data scarcity and increasing complexity. In contrast to the limited availability of system characteristics, highresolution data records of groundwater hydrographs are more generally available. Exploiting the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 38 publications
0
29
0
Order By: Relevance
“…The example showed that linear function between indices and system descriptors can have strongly deviating slopes among the three different response classes. Other factors that may be useful for preclassification are which flow system the well is tapping as well as local similarity, whose importance on groundwater dynamics were demonstrated by Giese et al (2020).…”
Section: Overarching Discussionmentioning
confidence: 99%
“…The example showed that linear function between indices and system descriptors can have strongly deviating slopes among the three different response classes. Other factors that may be useful for preclassification are which flow system the well is tapping as well as local similarity, whose importance on groundwater dynamics were demonstrated by Giese et al (2020).…”
Section: Overarching Discussionmentioning
confidence: 99%
“…It is also unclear how the boundary conditions should be included in the classification of groundwater systems as the responses of those systems to changes are not only the result of the aquifer properties but also of the unsaturated zone properties, land surface features and processes in adjacent and connected surface-water bodies (e.g. Giese et al 2020). Therefore, the classification of groundwater systems must include consideration of where the system boundaries are drawn and how the boundary processes are viewed.…”
Section: Groundwater Systems Similaritymentioning
confidence: 99%
“…Haaf et al (2020) evaluated which of those descriptors significantly influence the dynamic behaviour of groundwater levels. Giese et al (2020) applied the found descriptors to a selection of smaller case study areas. All descriptors defined in the framework of this research are described in Haaf et al (2020).…”
Section: Groundwater Systems Similaritymentioning
confidence: 99%
See 2 more Smart Citations